2019
DOI: 10.1007/s40430-019-1992-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of forced convection of Phan–Thien–Tanner fluid in slits and tubes of constant wall temperature with viscous dissipation

Abstract: In the present work, analytical solutions are presented for thermal convection of the linear Phan-Thien-Tanner fluid (LPTT) in slits and tubes of constant wall temperature by taking account of the viscous dissipation term. Unlike the similar previous studies in which the advection term was neglected in the heat transfer equation, it is considered in this investigation. A continuous relation between the Nusselt number and the Brinkman number is obtained. Expressions for the temperature distribution are derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…They showed that the effect of viscous dissipation could not be neglected when the wall temperature was uniform. For in-tube thermal conditions, Chaudhuri and Das [6] by using semi-analytical method, Teleszewski [7] for a tube with adiabatic wall and Newtonian fluid, Daghighi and Norouzi [8], and Dang [9] for a constant temperature wall condition, have been studied the effect of viscous dissipation in the thermal input region of a tube.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the effect of viscous dissipation could not be neglected when the wall temperature was uniform. For in-tube thermal conditions, Chaudhuri and Das [6] by using semi-analytical method, Teleszewski [7] for a tube with adiabatic wall and Newtonian fluid, Daghighi and Norouzi [8], and Dang [9] for a constant temperature wall condition, have been studied the effect of viscous dissipation in the thermal input region of a tube.…”
Section: Introductionmentioning
confidence: 99%